Unveiling the fundamental properties of sulphate based cathodes for next generation lithium ion batteries - Muthiah, Aravind (2018)
Lithium ion batteries lie at the heart of many of the portable electronics and automobiles in the modern world. By 2025 they will be responsible for storing energy equivalent to 12 times the energy released by the nuclear explosion at Hiroshima during the second World War. Thus, in addition to the high energy density capability of lithium ion batteries, safety assumes special significance. Li2M(SO4)2 (M=Fe, Co, Mn, Ni) class of sulphate based cathodes promise to meet both these criteria. High energy density on account of their higher operating voltage owing to the inductive effect of the sulphate group. Safety, due to the thermal stability offered by the covalent S-O bonds preventing oxygen release at high operating potentials. This thesis enabled an understanding of the electrochemical mechanism in Li2Fe(SO4)2 cathode through the x-ray absorption spectroscopy technique. Subsequently, this knowledge was instrumental in unveiling the reversible electrochemical activity of the Li2Mn(SO4)2 and Li2Co(SO4)2 analogues at 4.85 V and 5.02 V vs. Li, respectively. The redox mechanism was enabled through a combination of high energy ball milling to modify the cathode material and adoption of a novel composition of an electrolyte with sebaconitrile solvent. The study also investigated for the first time the synthesis of new solid solution series of bi-metallic sulphates and their structural, thermal, moisture sensitivity and magnetic properties. The maturity and commercial viability of the Li2Fe(SO4)2 cathode was evaluated by assembling an all iron full-cell and demonstrating its electrochemical stability. Finally, a techno-economic comparison of this full-cell with respect to the commercial cathode and anode chemistries was made, to place some perspective on the utility of this class of sulphate based cathodes.